Formation of 8-hydroxydeoxyguanosine by asbestos and man made mineral fibres. Issue 5 (May 1988) - Leanderson, P; Söderkvist, P; Tagesson, C; Axelson, O
Abstract : Samples of rockwool and glass fibre were compared with chrysotile fibres for their capacity to hydroxylate 2-deoxyguanosine to 8-hydroxydeoxyguanosine, a reaction that is mediated by formation of hydroxyl radicals. All three fibres produced 8-hydroxydeoxyguanosine in the absence of H2O2. The chrysotile fibres were most potent and produced about ten times more of the modified nucleoside than rockwool and glass fibre. This investigation shows that not only asbestos but also man made mineral fibres are able to modify nucleosides.